ACHIEVING PERFORMANCE THROUGH STRATEGIC AGILITY AND ENTREPRENEURIAL INNOVATION: AN EMPIRICAL RESEARCH IN SMEs SECTOR - Munawar, Fansuri; Kaniawati, Keni; Latifah, Ifa; Buana, Dwinto Martri Aji (Universitas Brawijaya, Indonesia, 2023)
Small and medium enterprises (SMEs) are often considered significant in developing countries like Indonesia. However, there are several problems regarding the quality of human resources and technical and non-technical skills, weaknesses in seizing opportunities, and lack of innovation. For this reason, SMEs need to be continuously developed both in quantity and quality, especially in improving their performance to contribute to economic development. Therefore, this study examines the factors directly or indirectly related to improving its performance. This study empirically predicts that strategic agility can influence entrepreneurial innovation and organizational learning. Furthermore, this study proposes a relationship between strategic agility, entrepreneurial innovation, and organizational learning on performance in SMEs. This research was conducted by taking samples from SMEs in the food and beverage, fashion, service, and other sectors. Sampling was conducted on 110 owners or managers of UKM in the Bandung, Garut, and Sumedang areas. Data analysis in this study used SEM-PLS. The results show that strategic agility positively relates to entrepreneurial innovation and organizational learning. Then, these findings show that organizational learning has the most significant influence on performance compared to strategic agility and entrepreneurial innovation. This study implies that SMEs can respond quickly to external changes, find creative solutions, and have agile capabilities in work processes. Recommendations for further research include environmental uncertainty moderating variables linking strategic agility and performance.